Bardet-Biedl syndrome associated with vaginal atresia: a case report - Uğuralp, Sema; Demircan, Mehmet; Cetin, Selma; Siğirci, Ahmet (The Turkish Journal of Pediatrics, 2003)
This is a case report of Bardet-Biedl syndrome associated with vaginal atresia diagnosed in a 15-year-old girl. She had mild mental retardation; obesity; nistagmus, retinitis pigmentosa and optic atrophy in both eyes; accessory digit on the left hand; polydactyly in lower extremities; a mobile, painful, nonfixed mass of 6 cm in diameter in the pelvic region; a palpable cystic mass in front of the rectal wall; and no vaginal opening. Secondary sex characteristics were determined. The vaginal atresia was distinguished from vaginal agenesis by the presence of proximal vagina in radiological examination.